Synthesis and Characterization of Some Transition Metal Complexes with Thiourea Derivatives - Esmadi, Fatima; Al-Masry, W. (Asian Journal of Chemistry, 2010)
Reactions of mono-, di-and tri-substituted thiourea with chloride salts of palladium, platinum, rhodium and iridium and with chlorocarbonyls of rhodium and iridium were carried out. The complexes were characterized by elemental analysis, spectroscopic data (UV and IR) and conductivity measurements. According to infrared data, thiourea derivatives are suggested to be sulfur bonded in all cases.